THE WALL-JET ELECTRODE AND THE STUDY OF ELECTRODE-REACTION MECHANISMS - THE EC (CATALYTIC) MECHANISM - Compton, R; Fisher, A; Tyley, G (Kluwer Academic Publishers, 1991)
The theory of EC′ (catalytic) reactions at the wall-jet electrode is developed using a computational procedure based on the Expanding Grid Backwards Implicit method. In particular, it is shown that the variation of the transport limited current with solution flow rate provides a means of characterising the EC′ mechanism. A working curve is presented which shows how the effective number of electrons transferred depends on a normalized rate constant and this permits the analysis of experimental data and the deduction of the homogeneous rate constant of the catalytic chemical reaction, for arbitrary electrode geometry, without recourse to further computation. © 1990 Chapman and Hall Ltd.